Walsh, Daphne. New Perlican Photograph of a man on skis with a dog. - Barrett, Terra (1940)
A photograph of William Hobbs on skis with a black and white dog. Above the photo says "Family Memories" and below the photo says "Dad." The photo was printed by Kodak circa late 1940s. Black Duck Siding.